Interações entre espécies exóticas invasoras e espécies nativas: calitriquídeos no Parque Nacional da Serra dos Órgãos, RJ. - Pereira, Daniel Gomes (2009)
Wildlife management can be defined as the manipulation of populations of wild animals, the its habitats and interactions, with the purpose of getting to a determined population management objective. The introduction of exotic animal species and the consequences of the permanence of these invaders in the new environment is increasingly being studied in order to evaluate the possible impacts. Two species of primates, Callithrix jacchus (common marmoset) and C. penicillata (black pincelled marmoset) which occur respectively at Caatinga / Atlantic forest of Norwest and Brazilian Cerrado, were introduced many years ago in other regions of Atlantic forest, settling and occupying the area of other native species of callitrichids, such as C. aurita (buffy tufted ear marmoset), a species threatened of extinction. The association between native and exotic primates is little studied and could generate competition for resources and permutation of parasites, which constitute a threat to the preservation of native species. The value of the Preservation Units as research resource has been recognized for a long time. The implementation and effective handling of Preservation Units constitute an enormous challenge. The objective of this study was to contribute to the preservation of native primate species in Preservation Units. Through the observation of occurrence of native and exotic species of primates at National Park of Serra dos Órgãos (PARNA-SO) and the evaluation of the environmental perception of the residents around the PARNA-SO, it is desired to proposing management strategies for the preservation of C. aurita. Combining the evident rarity and low population density of C. aurita with the great competitive and generalist capacity of C. penicillata in habitat needs, food resources and genetic introduction, it is possible to consider the biologic invasion of C. penicillata as an important factor for dynamics of C. aurita populations at PARNA-SO. Management strategies include: verification of other populations of C. aurita free from biologic invasion of C. penicillata; removal of all C. penicillata individuals and hybrids; presentation of C. aurita to the population (environmental consciousness-raising); combat the exotic invader species.